Characterization of Aspergillus section Flavi isolated from fresh chestnuts and along the chestnut flour process. (February 2018) - Prencipe, Simona; Siciliano, Ilenia; Contessa, Cecilia; Botta, Roberto; Garibaldi, Angelo; Gullino, Maria Lodovica; Spadaro, Davide
Abstract: An extensive sampling of Aspergillus section Flavi considered to be the main agent responsible for aflatoxin contamination, was carried out in the field and along the processing phases of chestnut flour production in 2015. Fifty-eight isolates were characterized by means of biological, molecular and chemical assays. The highest incidence of Aspergillus section Flavi was found in the field. The identification of the isolates was based on β-tubulin and calmodulin gene sequences. A. flavus was found to be the dominant species, and this was followed by A. oryzae var effusus, A. tamarii, A. parasiticus and A. toxicarius. Nineteen percent of the strains produced aflatoxins in vitro and forty percent in vivo . The pathogenicity assay on chestnut showed 56 virulent strains out of 58. The molecular, morphological, chemical and biological analyses of A. flavus strains showed an intraspecific variability. These results confirm that a polyphasic approach is necessary to discriminate the species inside the Aspergillus section Flavi . The present research is the first monitoring and characterization of aflatoxigenic fungi from fresh chestnut and the chestnut flour process, and it highlights the risk of a potential contamination along the whole chestnut production chain. Highlights: Aspergillus section Flavi were characterized along the chestnut flour chain. A. flavus was the dominant species, followed by other Aspergillus species. Aflatoxins were produced in vitro and in vivo by 11.6% and 39.5% of the strains. The pathogenicity assay on chestnut showed 56 virulent strains out of 58. A polyphasic approach is necessary to discriminate the species in the section Flavi.